Clean and Contain: Initial Development of a Measure of Infection Prevention Behaviors During the COVID-19 Pandemic. Issue 9 (28th August 2020) - Toussaint, Loren L; Cheadle, Alyssa D; Fox, Jesse; Williams, David R
Abstract: Background: The Centers for Disease Control and Prevention (CDC) offer behavioral guidance to prevent the spread of infectious diseases like COVID-19. Cleaning (e.g., cleaning surfaces, washing and sanitizing hands) and containing (e.g., covering coughs, keeping distance from others, especially sick people) behaviors are recommended. Purpose: To develop the Clean and Contain Measure, a brief measure of compliance with CDC recommendations for prevention of infectious disease, and validate the measure in individuals experiencing the COVID-19 pandemic. Methods: Participants were recruited from Amazon Mechanical Turk and social media. Results: In Study 1 ( N = 97), exploratory factor analysis revealed two scales: (a) five items assessing cleaning behaviors and (b) four items assessing containing behaviors. Simple structure was obtained and alpha coefficients for both scales were >.83. In Studies 2 ( N = 204) and 3 ( N = 527), confirmatory factor analysis verified the identical factor structure found in Study 1. All loadings were statistically significant at p < .001. Alpha coefficients for both scales were >.84 for Studies 2 and 3. Conclusions: Our measure is a reliable and valid indicator of compliance with cleaning and containing health behaviors that help to prevent the spread of diseases like COVID-19. Future research should replicate construct validity in more diverse samples and continue to refine items, examine construct validity, including predictive and discriminant validity, and improve the measure for future use. With continued use and refinement, this measure could allow health officials and researchers to accurately assess compliance with important infection prevention behavior guidelines. Abstract : Health behavior measurement is critical in limiting the spread of infectious diseases like COVID-19. This 9-item measure assesses compliance with important infectious disease prevention behaviors.